PENGARUH BOOK TAX DIFFERENCES, UKURAN PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP PERTUMBUHAN LABA - Fais Hidayat; Benarda (Jurnal Nusa Akuntansi, 2026)
This study aims to examine the effect of Book Tax Differences, Firm Size, and Operating Cash Flow on Profit Growth in consumer non-cyclicals sector companies, specifically in the food and beverage sub-sector, listed on the Indonesia Stock Exchange for the period 2020–2024. The type of research used is quantitative research with secondary data sources, utilizing a purposive sampling method based on predetermined criteria. The results of this study indicate that Book Tax Differences, Firm Size, and Operating Cash Flow simultaneously have a significant effect on Profit Growth. Partially, Book Tax Differences has a significant effect on Profit Growth. Firm Size, on the other hand, does not have a significant partial effect on Profit Growth. Meanwhile, Operating Cash Flow partially has a significant effect on Profit Growth.